Investigation of the relation of the leg volume to the anaerobic power values in the elite swimmers - Akyüz, Ö.; Isildak, K.; Tas, M.; Akyüz, M.; Turna, B. (European Journal of Physical Education and Sport Science, 2018)
The purpose of this study is to investigate the relationship of leg volume to the anaerobic power values in elite swimmers. The average age of the participants was 16.50 ± 52 years, the average age of the sport was 7.83 ± 1.69 years, the average height was 176.36 ± 6.71 cm, body weight average of 66.16 ± 8.56 kg who participated in the swimming competitions and participated in the swimming competitions regularly in Antalya Kulaç Swimming Specialized Sports Club. Right leg volume, left leg volume, total leg volume and anaerobic strength tests of the players were taken. There was a significant positive correlation between the right leg volume and the anaerobic power relationship, the left leg volume with the anaerobic relationship, and the total leg volume with the anaerobic power association values (p <0,05). As a result, the leg volume in the elite swimmers has positive anaerobic results. For this reason, it is suggested that the training programs to be applied should include mainly leg exercises.